Pengaruh Pemberian Berbagai Konsentrasi Indole-3-Butyric Acid (IBA) dan Lama Perendaman terhadap Pertumbuhan Stek Batang Timi (Thymus vulgaris L.) - Khodijah Wafia; Karno Karno; Florentina Kusmiyati (Universitas Sebelas Maret, 2021)
The method of thyme stem cutting needs to be developed to produce better roots to support growth. The study aims to examine the response of thyme stem cuttings to various concentration of IBA and time soaking. The research was carried out on January – March 2020 in screen house PT. INDMIRA, Sleman, Yogyakarta and the Physiology and Plant Breeding Laboratory of the Faculty of Animal and Agricultural Science, Diponegoro University. The method used was a completely randomized design with a factorial 4×3 with 5 replications. The first factor was a various concentration of IBA: A0 (0 ppm), A1 (100 ppm), A2 (250 ppm), and A3 (500 ppm). The second factor was the time soaking: B1 (5 minutes), B2 (10 minutes), and B3 (15 minutes.) The results showed that IBA concentration has no significant effect for root dry weight, while the time soaking has significant effect for all parameters. Soaking thyme stem cuttings at an IBA 250 ppm for 10 minutes gave the best results on plant length, the number of leaves, root length, and root dry weight, but soaking in water (without IBA) for 5 minutes was able to give the best number of percentage of life cuttings (85%) so that giving IBA had no needed.